(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the documentary literature work portrait is a part of sketch description of real historical person because in a very short text area according to laconic way of thought expression the author doesn’t have an opportunity for portrait creation of full value. But even in this case the reader can see some kind of reduced typification and individualization of character through his appearance description (face, clothes, pos, gestures, and look), way of behaving, speech dynamics, ethnical and social belonging, and sex.